Origin of Plutonium-244 in the Early Solar System - Maria Lugaro; Andrés Yagüe López; Benjámin Soós; Benoit Côté; Mária Pető; Nicole Vassh; Benjamin Wehmeyer; Marco Pignatari (Universe, 2022)
We investigate the origin in the early Solar System of the short-lived radionuclide <semantics>244</semantics>Pu (with a half life of 80 Myr) produced by the <semantics>rapid</semantics> (r) neutron-capture process. We consider two large sets of r-process nucleosynthesis models and analyse if the origin of <semantics>244</semantics>Pu in the ESS is consistent with that of the other r and <semantics>slow</semantics> (s) neutron-capture process radioactive nuclei. Uncertainties on the r-process models come from both the nuclear physics input and the astrophysical site. The former strongly affects the ratios of isotopes of close mass (<semantics>129</semantics>I/<semantics>127</semantics>I, <semantics>244</semantics>Pu/<semantics>238</semantics>U, and <semantics>247</semantics>Pu/<semantics>235</semantics>U). The <semantics>129</semantics>I/<semantics>247</semantics>Cm ratio, instead, which involves isotopes of a very different mass, is much more variable than those listed above and is more affected by the physics of the astrophysical site. We consider possible scenarios for the evolution of the abundances of these radioactive nuclei in the galactic interstellar medium and verify under which scenarios and conditions solutions can be found for the origin of <semantics>244</semantics>Pu that are consistent with the origin of the other isotopes. Solutions are generally found for all the possible different regimes controlled by the interval (<semantics>δ</semantics>) between additions from the source to the parcel of interstellar medium gas that ended up in the Solar System, relative to decay timescales. If r-process ejecta in interstellar medium are mixed within a relatively small area (leading to a long <semantics>δ</semantics>), we derive that the last event that explains the <semantics>129</semantics>I and <semantics>247</semantics>Cm abundances in the early Solar System can also account for the abundance of <semantics>244</semantics>Pu. Due to its longer half life, however, <semantics>244</semantics>Pu may have originated from a few events instead of one only. If r-process ejecta in interstellar medium are mixed within a relatively large area (leading to a short <semantics>δ</semantics>), we derive that the time elapsed from the formation of the molecular cloud to the formation of the Sun was 9-16 Myr.